Insiden Kecelakaan Mencederai Harga Saham - Azzahrani, Farahdina Safa; Herlinda Maya Kumala Sari; Sriyono (Paradoks : Jurnal Ilmu Ekonomi, 2025)
This study is motivated by the impact of transportation accidents on investor confidence and stock price volatility in transportation companies. The main objective is to examine the effect of profitability, firm size, and firm growth on stock prices in the transportation sector following accident incidents. This research employs a quantitative approach using secondary data derived from the annual reports of transportation companies listed on the Indonesia Stock Exchange (IDX). The sample was determined through purposive sampling based on specific criteria relevant to transportation accident cases. A total of 11 companies were selected as the research sample covering the period 2022–2024. Data analysis was conducted using EViews 12 software. The findings reveal that profitability, firm size, and firm growth simultaneously affect stock prices. In general, transportation accident incidents exert a negative pressure on the stock performance of transportation companies listed on the IDX. The study confirms that internal factors such as profitability, firm size, and growth remain crucial determinants of stock prices, particularly when companies face external shocks such as transportation accidents. The implication is that companies need to strengthen financial performance and ensure transparent information disclosure to maintain stock value stability and mitigate the adverse effects of unexpected events.